A companion to the Neronian age - Buckley, Emma; Dinter, Martin (Blackwell companions to the ancient world, 2013)
Introduction: The Neronian (Literary) "Renaissance" / Martin T. Dinter -- Part I. Nero -- The Performing Prince / Elaine Fantham -- Biographies of Nero / Donna W. Hurley -- Nero the Imperial Misfit : Philhellenism in a Rich Man's World / Sigrid Mratschek -- Part II. The Empire -- The empire in the age of Nero / Myles Lavan -- Apollo in arms : Nero at the frontier / David Braund -- Domus Neroniana : The Imperial Household in the Age of Nero / Michael J. Mordine -- Religion / Darja Eterbenc Erker -- Neronian Philosophy / Jenny Bryan -- Part III. Literature, Art and Architecture -- Seneca, Apocolocyntosis / Christopher L. Whitton -- The Carmina Einsidlensia and Calpurnius Siculus' Eclogues / John Henderson -- Seneca's Philosophical Writings : Naturales Quaestiones, Dialogi, Epistulae Morales / Jonathan Mannering -- Senecan Tragedy / Emma Buckley -- Lucan's Bellum Ciuile / Philip Hardie -- Petronius' Satyrica / Tom Murgatroyd -- Persius / Marden Fitzpatrick Nichols -- Columella, De Re Rustica / Christiane Reitz -- Literature of the World : Seneca's Natural Questions and Pliny's Natural History / Aude Doody -- Greek Literature Under Nero / Dirk Uwe Hansen -- Buildings of an Emperor : how Nero transformed Rome / Heinz-Jürgen Beste and Henner von Hesberg -- Portraits of an Emperor : Nero and the Sun / Marianne Bergmann -- Neronian Wall-Painting : A Matter of Perspective / Katharina Lorenz -- Part IV. Reception -- Nero in Jewish and Christian Tradition from the First Century to the Reformation / Harry O. Maier -- Haec monstra edidit : Translating Lucan in the early seventeenth century / Yanick Maes -- Haunted by Horror : The Ghost of Seneca in Renaissance Drama / Susanna Braund -- "Fantasies so varied and bizarre" : The Domus Aurea, the Renaissance, and the "grotesque" / Michael Squire -- Epilogue -- Nachwort: Nero from Zero to Hero / Miriam Griffin